Examining the Relationship Between Tax Revenue and Economic Growth in Indonesia Through the Endogenous Growth Model - Yossinomita, Y.; Haryadi, H.; Nainggolan, S.; Zulfanetti, Z. (Review of Business and Economics Studies, 2025)
The aim of this study is to analyze the causal relationship between tax revenues and economic growth in Indonesia using an endogenous growth economic model. The causality analysis employed a multivariate setup using a vector autoregression approach, with the Toda–Yamamoto method serving as the causality test. Using time series data from 1983 to 2021, the research findings indicate that the control variables — capital, labor, foreign direct investment, government spending, inflation, and exchange rates — reflect innovation mechanisms and technological progress or total factor productivity in the endogenous growth model, which captures the relationship between tax revenues and economic growth in Indonesia. The results of the causality test using the Toda–Yamamoto method show that tax revenues and economic growth influence each other; tax revenues help boost economic growth, and at the same time, higher economic growth leads to more tax revenues. The authors concluded that, in addition to tax revenue causing or encouraging economic growth through financing economic activities, increased economic growth and activity will also raise the amount of tax revenue, both from the tax base and from nominal tax revenue determined by economic growth.